Avaliação da digestão de amostras de piche assistida por radiação microondas e determinação de metais por ICP OES - Moura, Fernando Antonio Lins de (2007)
This work reports the development of analytical methodologies for the determination of metals in samples of pitch after their digestion employing different strategies based on microwave radiation. The digestion process was monitored by measuring residual carbon content and metals in the samples, both by ICP OES and the obtained results compared against TOC and INAA measurements. All experimental work was performed using high vacuum distilled pitch from petroleum aromatic residua containing 95, 4 ± 0.1 % of carbon. To detect the main factors that influenced the digestions procedures and the interactions between them, tests were carried out using a two -level factorial design. The variables studied in pressurized system were: 220°C time digestion ( 5 and 20 min), H2O2 and HCl volumes ( 1 and 3 ml) and sample mass (250 and 500 mg) At these conditions residual carbon content between 38 a 51% was obtained and Fe, Cu and Zn results agreed higher than 90% when compared with INAA results . A gradual encapsulated sample addition strategy was applied to focused microwave. A program power irradiation based was implemented divided into two steps of irradiation 120W /40 min and 210W/20min. A two-level factorial design experiment was carried out to evaluate the influence of HNO3 and H2SO4 volume (0 and 50%), digestion mixture total volume (5 and 7 ml) and H2O2 (3 and 5 ml) on RCC and metal concentrations in digestates. At these conditions were obtained RCC values between 0,7 and 26%, Fe agreed from 16 to 100% and Cu from 29 to 68% however Zn, Mn e V concentrations were lower than minimum detection level and were not detected . The microwave assisted sample combustion procedures were developed in a quartz vessel inserted in a standard PFA vessel. The sample was weighed in a treated filter paper and placed in quartz holder. The holder was positioned into the vessels and 50µL of ammonium nitrate was added as an igniter for the combustion procedure . Vessels were closed and pressurized with oxygen to 290 psi. The ignition was performed by 1400W microwave radiation applied for 10 min. Residual carbon content was not measured in this case and metal recoveries agreed 19 % to Co, 67% to Cu and 73 % to Zn.